(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Using the systematic approach, the possible basing schemes of the workpieces in the machining attachments have been discovered and systematized with a view to their use in automated design. The analysis shows that the use of the proposed systematization in computer-aided design is significantly more rational, since the structure reflects the sequence of choice of the optimal basing scheme - analysis of the theoretical basing scheme, analysis of the geometry of the workpiece, formation of the possible list of the basing schemes. An analysis was performed with the help of which the criteria for geometric compatibility were revealed, allowing to make a choice of a basing scheme, satisfying the geometric shape of the workpiece. An algorithm for selection of locators has been developed. The development is part of a system for automated design of fixtures for locating of workpieces during machining.